ChemInform Abstract: A Palladium‐Nanoparticle and Silicon‐Nanowire‐Array Hybrid: A Platform for Catalytic Heterogeneous Reactions. Issue 30 (29th July 2014) - Yamada, Yoichi M. A.; Yuyama, Yoshinari; Sato, Takuma; Fujikawa, Shigenori; Uozumi, Yasuhiro
Abstract The title catalyst is applied to hydrogenation of an alkene (I), hydrogenolysis of nitrobenzene (III), hydrosilylation of an α, β‐unsaturated aldehyde (V), C—H bond functionalization reactions of heteroaromatic compounds [(XI) and (VIII)], and Mizoroki‐Heck reaction (XIII).